Standardization of science process skills (SPS) assessment instruments in microbiology labs - Posangi, Nona Wingti; Hasan, Ani M; Dama, Lilan (Inornatus: Biology Education Journal, 2018)
This study aims to standardize science process skills (SPS) instruments in microbiology labs. This Type research is quantitative descriptive, which focuses on standardizing instruments. The research subjects were students of the Biology Education Department of FMIPA Universitas Negeri Gorontalo who programed microbiology courses. Validation was carried out by three experts. The results showed that the value of validity was 4.95 in aspects of the assessment of items on SPS and 4.85 in aspects of language ass essment. The results of measurements on science process skills of students have obtained an average of 3.00 in trials I and 3.37 in trial II. The reliability of the instrument in the first trial was 0.81 and in the second trial was 0.82. The results of the research obtained indicate that KPS skill instruments are valid and reliable. The instrument can be used to measure student science process skills, especially in microbiology courses. Future research can compile PPP instruments in other subjects.